2018
DOI: 10.1039/c8ta00437d
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on the surface and interfacial properties of Ni3P for the hydrogen evolution reaction

Abstract: DFT study on the catalytic activity for HER on low-index Ni3P crystal surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Researchers have revealed that catalysts, even for the same crystal, with different facets may show very different HER properties . This facet‐dependent HER activity could be explored and understood by density functional theory (DFT) . For example, Feng et al .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Researchers have revealed that catalysts, even for the same crystal, with different facets may show very different HER properties . This facet‐dependent HER activity could be explored and understood by density functional theory (DFT) . For example, Feng et al .…”
Section: Introductionsupporting
confidence: 80%
“…In this paper, a star symbol (*) denotes as a free adsorption site on the surface, so the H* symbol means a hydrogen atom adsorbed on an adsorption site of the surface. Since the intermediate adsorbed H* is needed in both these two mechanisms, one can use the Gibbs free energy of H* adsorption (ΔG H* ) to describe the HER electrocatalytic activity, which was proposed by Nørskov and co‐workers and has been widely used in the theoretical research area of HER ,,,. The Gibbs free energy of absorbed H* (ΔG H* ) is calculated by Equation : trueΔGH*=ΔEH*+ΔEZPE-TΔS …”
Section: Methodsmentioning
confidence: 99%
“…Among the different surface terminations, that is, P‐rich, stoichiometric, and Ni‐rich, all the stable surface energies have a negative slope (Figure b). This means that the P‐rich surfaces with different terminations are stable, which is in agreement with previous results . The surface energies follow the order of (110)C < (001)A < (101)C < (100)A < (111)C. The surface energy of (110)C, as the most stable surface of Ni 12 P 5 , is ≈1.24 J m −2 when Δ μ p = −0.48 eV.…”
Section: Resultssupporting
confidence: 91%
“…This means that the P-rich surfaces with different terminations are stable, which is in agreement with previous results. [21] The surface energies follow the order of (110)C < (001)A < (101)C < (100)A < (111)C. The surface energy of (110)C, as the most stable surface of Ni 12 P 5 , is %1.24 J m À2 when Δμ p ¼ À0.48 eV. Furthermore, the surface energies are affected by the coordination number of surface Ni atom, as shown in Figure 2a.…”
Section: Stability Of Ni 12 Pmentioning
confidence: 99%
“…Among this, the coordination of (100) and (001) facets are more stable and surface energy nearly 0.1 eV/Å 2 , while (010) facets was found to be least in stability under vacuum condition. Thus, the phosphides with the rich transition metals or rich phosphorous percentage trigger the intrinsic activity of OER and HER in water electrolysis [78] . In addition, the concept of surface oxide/hydroxide layers formed during OER over the metal phosphides as shell/cores types with phosphides, borides and nitrides behave was studied as superior catalytic system in water electrolysis [89] .…”
Section: Mechanical Aspects Of Metal Phosphides In Terms Of Activity and Stabilitymentioning
confidence: 99%